Mixed-Methods Analysis of Oral Proficiency of Tertiary ESL Students: Basis for Pedagogical Intervention - Bante, Maribeth A. (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
State universities and colleges in the Philippines adopted English as the primary medium of instruction, with speaking playing a significant role as part of the four basic skills when learning a language. Therefore, the study explored the perceived oral proficiency of tertiary students in a state university, with ESL teachers suggesting possible interventions to improve the effectiveness of teaching and learning oral English skills. A sequential explanatory mixed methods design was used, where simple random sampled respondents among tertiary students answered online survey questionnaires, while conveniently sampled ESL teachers answered the supplementary open-ended questions based on the initial quantitative results. Through descriptive analysis, students were found to have generally decent oral proficiency skills, with strong to neutral agreement on the influence of environmental and psychological factors. The teachers then interpreted the quantitative results, saying that for oral proficiency skills, students had satisfactory skills, a lack of self-assurance in those skills, and a need for targeted support for those skills, while for environmental and psychological factors, students had confused self-concepts, primarily extrinsic motivation for learning, and an appreciation for their learning environment. ESL teachers suggested speech practice and integration, interactive activities, and real-world experiences as pedagogical interventions for oral proficiency and motivating experiences, acceptance of mistakes, and safe learning environments for the factors of oral proficiency. Besides taking into consideration the possible pedagogical interventions, the researcher recommended expanding research on the structures and variables that affect oral proficiency skills.